2010
DOI: 10.1159/000318818
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Thrombosis in Ulcerative Colitis

Abstract: Left ventricular thrombi usually occur in the setting of an acute myocardial infarction, left ventricular aneurysm, or dilated cardiomyopathy. In the absence of ventricular wall motion abnormalities, they are rare. This report describes a patient with ulcerative colitis in whom two-dimensional echocardiography revealed a left intraventricular mass. Thrombosis in ulcerative colitis is a serious condition and can occur in a very young population. This case also shows that left ventricular thrombi can occur in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
0
13
0
2
Order By: Relevance
“…But the cause of MI was left ventricular thrombosis and there was no coronary atherosclerosis observed. [ 19 , 20 ] Another young man was diagnosed of atherogenic MI after a recent flare of UC and enteropathic arthritis. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…But the cause of MI was left ventricular thrombosis and there was no coronary atherosclerosis observed. [ 19 , 20 ] Another young man was diagnosed of atherogenic MI after a recent flare of UC and enteropathic arthritis. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…9 More than half of the thrombotic events occur during an exacerbation of inflammatory bowel disease. 11 In parallel with this, the risk for thrombosis correlates with the disease activity of inflammatory bowel disease. 12 Cases of spontaneous ventricular thrombosis also have been reported in patients with inflammatory bowel disease in the age range of 28-42 years.…”
Section: R Isk Factors For Thrombogenesis Have Beenmentioning
confidence: 91%
“…12 Cases of spontaneous ventricular thrombosis also have been reported in patients with inflammatory bowel disease in the age range of 28-42 years. [11][12][13][14][15][16] In all cases, the patients were asymptomatic, and ventricular thrombosis was detected as an incidental finding during an acute flare-up of inflammatory bowel disease. Except for one instance of right ventricular thrombosis, all other cases of ventricular thrombosis developed in the left ventricle.…”
Section: R Isk Factors For Thrombogenesis Have Beenmentioning
confidence: 99%
“…Chin et al reported a left ventricular thrombus with systemic emboli in a patient with ulcerative colitis and cocaine abuse [3] . Another report of left ventricular thrombus manifested with additional neurological symptoms [4] . Finally, Urgesi et al described a case of a young woman affected by protein C deficiency, who, during a clinical recurrence of ulcerative colitis, developed a spontaneous right ventricular thrombus and pulmonary embolism [1] .…”
Section: Post Gadolinium Two Non-enhancing Lesions (Arrows) the Mmentioning
confidence: 99%